2019
DOI: 10.1021/acsmedchemlett.9b00350
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-oxindole Piperidines and 3-(Azetidin-3-yl)-1H-benzimidazol-2-ones as mGlu2 Receptor PAMs

Abstract: Starting from two weak mGlu2 receptor positive allosteric modulator (PAM) HTS hits (4 and 5), a molecular hybridization strategy resulted in the identification of a novel spiro-oxindole piperidine series with improved activity and metabolic stability. Scaffold hopping around the spiro-oxindole core identified the 3-(azetidin-3-yl)-1H-benzimidazol-2-one as bioisoster. Medicinal chemistry optimization of these two novel chemotypes resulted in the identification of potent, selective, orally bioavailable, and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…THRX-195518 is a molecule with a piperidine structure and a molecular weight of 598.73 g/mol (Figure 3). The literature reports that most PAM ligands exhibit a pyrimidine structure [42,43]. When examining drug-likeness and ADMET analysis for THRX-195518 and the other two mGlu2 activators in our study (LY 379268 and JNJ-46281222), it is observed that the molecules exhibit drug-likeness (Table 1).…”
Section: Discussionmentioning
confidence: 59%
“…THRX-195518 is a molecule with a piperidine structure and a molecular weight of 598.73 g/mol (Figure 3). The literature reports that most PAM ligands exhibit a pyrimidine structure [42,43]. When examining drug-likeness and ADMET analysis for THRX-195518 and the other two mGlu2 activators in our study (LY 379268 and JNJ-46281222), it is observed that the molecules exhibit drug-likeness (Table 1).…”
Section: Discussionmentioning
confidence: 59%
“…These methods are suitable for scaffold hopping because they assess properties important for biological recognition and not just underlying atom connectivity. We have previously developed optimal implementations of these approaches and applied them to identify mGlu2 PAM scaffolds. , Here, our approach was similar and aimed at replacing the central scaffold, the triazolopyridine in 2a , with alternative heterocyclic ring systems. We have databases of prefragmented compounds from internal and commercial sources and use these to search and retrieve alternative 3D-similar heterocycles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Within our laboratories, a long-lasting research effort in the mGlu 2 PAM field in collaboration with Addex Therapeutics resulted in the identification of our clinical lead JNJ 40411813 ( 1 , Figure ) from a series of pyridones. , Subsequent backup programs guided by scaffold hopping approaches led to the development of potent and selective imidazopyridine , and triazolopyridine mGlu2 PAMs. , More recently, we again showed how computationally guided scaffold hopping led to the discovery of a spirooxindole series of mGlu2 PAMs …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation